The Slavery of Mystical Creature on The Golem and The Jinni - Susilawati, E (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Golem is an artificial creature that made from clay and water with incantations and spells by a man (rabbi), It made to serve its creator. It well known as a creature of Jewish Mythology. The object of this research is The Golem, Chava on the novel with tittle “The Golem and The Jinni” by Helene Wecker. In this novel the character of Golem described as a good creature and has intimate relationship with the Jinni. Actually it is different as the others stories of Golem that always described as an evil creature who can destroy or kill the creator. The purpose of this research is to describe narratively the slavery of mystical creature, especially Golem and how Golem can survive and get along with human. Chava hardly refuse the orders from her master to kill human and do bad things even she was threaten got killed by her master. Due to this research found there was a friction role of Golem, in the past it is made to protect the master or the group from the harm thing or enemy while in this novel it is made to be a wife and she had a feeling and look as well as human. She could make a relationship with both human and the other creature such as Jinni. This research hopefully can be used as a source of cultural studies and narrative approach.